Upgradation of Iron Ore Fines and Slime by Selective Flocculation Using Surface-Active Agents, Settling Study, and Characterization of the Beneficiation Waste for Value Addition - Jyotirmoy Sarma; Sanchayita Rajkhowa; Sekh Mahiuddin (Journal of Chemistry)
Washing of iron ore fines and slime (10% and 25% w/v, slurry concentrations) with two types of surface-active agents (sodium humate (synthesized) and AD 200 (commercial)) at varying concentrations at pH 8 was conducted for ascertaining the efficacy of dispersants in beneficiating the low-grade iron ores. The beneficiation process follows the “selective dispersion-cum-settling technique.” The process results in the formation of a dispersed phase rich in gangue minerals and a settled phase of predominantly active hematite mineral. The stability of dispersed phase (DP) was evaluated by determination of the percentage solid content in the DP. Settling tests were performed. First-order kinetic models have been applied to the dispersion-cum-settling behaviour of both the samples, and evaluated kinetic parameters were found to have good agreement with experimental data. Removal of gangue minerals from iron ore depends on the pH of the slurry, concentration of the slurry, and concentration of the surface-active agent used. The surface-active agents at pH 8 produce ∼1.2–1.5 times more stable suspension in the case of iron ore fines and slimes than that of without surface-active agent. They significantly remove gangue minerals and increase the iron value ∼2–7% with ∼58–74% recovery depending on the experimental conditions. The concentrates collected satisfy the required specifications (Al203/Fe < 0.05 and Al203/Si02 < 1). The gangues in the dispersed phase as characterised by “SEM-EDXA” are mostly clay-bearing minerals like kaolinite, goethite, chlorite, and alumina-silicate minerals. Heat treatment causes distortion of clay minerals present in the dispersed phase and also indicates the complex nature of the gangue minerals.